2011
DOI: 10.1038/ismej.2011.177
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of β-diversity and assembly mechanisms in a bacterial metacommunity

Abstract: The turnover of community composition across space, b-diversity, is influenced by different assembly mechanisms, which place varying weight on local habitat factors, such as environmental conditions and species interactions, and regional factors such as dispersal and history. Several assembly mechanisms may function simultaneously; however, little is known about how their importance changes over time and why. Here, we implemented a field survey where we sampled a bacterial metacommunity consisting of 17 rock p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
122
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 49 publications
5
122
3
Order By: Relevance
“…Landscape features such as glaciers have the potential to create strong landscape heterogeneity by dictating coarse-scale physicochemical characteristics of habitats over time and space. Hydrogeochemical conditions, disturbance as well as spatial connectivity between aquatic systems can be altered by glaciers, and it has been shown that these mechanisms can influence BCC (Sekar et al, 2002;Frey et al, 2009;Langenheder et al, 2011). In contrast, lake outlet streams or groundwater-fed streams provide more spatiotemporal stability and a more homogeneous landscape (Tockner et al, 1997;Brown et al, 2003), and the smaller fluctuations in physicochemical characteristics in such habitats cause reduced variability in bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Landscape features such as glaciers have the potential to create strong landscape heterogeneity by dictating coarse-scale physicochemical characteristics of habitats over time and space. Hydrogeochemical conditions, disturbance as well as spatial connectivity between aquatic systems can be altered by glaciers, and it has been shown that these mechanisms can influence BCC (Sekar et al, 2002;Frey et al, 2009;Langenheder et al, 2011). In contrast, lake outlet streams or groundwater-fed streams provide more spatiotemporal stability and a more homogeneous landscape (Tockner et al, 1997;Brown et al, 2003), and the smaller fluctuations in physicochemical characteristics in such habitats cause reduced variability in bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that many microorganisms have different abundances across many connected environments and gradients (e.g. Langenheder et al 2012, Ruiz González et al 2015, and, of course, different habitats vary in their productivity. For example, an oligotroph in a soil habitat may, with no fundamental alteration to its physiology, fall more along the copiotrophic end of a trophic continuum than it would in a neighboring wetland habitat, though it may naturally occur in both localities.…”
Section: Local Rarity Along Habitat Gradients Linked By Regional Metamentioning
confidence: 99%
“…For example, pH (1)(2)(3)(4), temperature (5), organic carbon (6,7), and salinity (8,9) have all been identified as major drivers of microbial niche differentiation in a variety of natural habitats. Spatial distance (10)(11)(12)(13) and temporal distance (14)(15)(16) can also structure microbial communities due to environmental heterogeneity, dispersal limitation, historical contingency, stochastic events, and disturbances. Extreme environments, such as acidic systems, can be useful as model systems for the analysis of microbial niches because of the limited biological diversity and available number of energy-deriving reactions (17)(18)(19).…”
mentioning
confidence: 99%